Frequency‐dependent facilitation of synaptic throughput via postsynaptic NMDA receptors in the nucleus of the solitary tract. (3rd November 2014) - Zhao, Huan; Peters, James H.; Zhu, Mingyan; Page, Stephen J.; Ritter, Robert C.; Appleyard, Suzanne M.
Key points: Hindbrain NMDA receptors play important roles in reflexive and behavioural responses to vagal activation. NMDA receptors have also been shown to contribute to the synaptic responses of neurons in the nucleus of the solitary tract (NTS), but their exact role remains unclear. In this study we used whole cell patch‐clamping techniques in rat horizontal brain slice to investigate the role of NMDA receptors in the fidelity of transmission across solitary tract afferent–NTS neuron synapses. Results show that NMDA receptors contribute up to 70% of the charge transferred across the synapse at high (>5 Hz) firing rates, but have little contribution at lower firing frequencies. Results also show that NMDA receptors critically contribute to the fidelity of transmission across these synapses during high frequency (>5 Hz) afferent discharge rates. This novel role of NMDA receptors may explain in part how primary visceral afferents, including vagal afferents, can maintain fidelity of transmission across a broad range of firing frequencies. Abstract: Neurons within the nucleus of the solitary tract (NTS) receive vagal afferent innervations that initiate gastrointestinal and cardiovascular reflexes. Glutamate is the fast excitatory neurotransmitter released in the NTS by vagal afferents, which arrive there via the solitary tract (ST). ST stimulation elicits excitatory postsynaptic currents (EPSCs) in NTS neurons mediated by both AMPA‐ and NMDA‐type glutamate receptors (‐Rs). Vagal afferents exhibit a high probability of vesicle release and exhibit robust frequency‐dependent depression due to presynaptic vesicle depletion. Nonetheless, synaptic throughput is maintained even at high frequencies of afferent activation. Here we test the hypothesis that postsynaptic NMDA‐Rs are essential in maintaining throughput across ST–NTS synapses. Using patch clamp electrophysiology in horizontal brainstem slices, we found that NMDA‐Rs, including NR2B subtypes, carry up to 70% of the charge transferred across the synapse during high frequency stimulations (>5 Hz). In contrast, their relative contribution to the ST‐EPSC is much less during low (<2 Hz) frequency stimulations. Afferent‐driven activation of NMDA‐Rs produces a sustained depolarization during high, but not low, frequencies of stimulation as a result of relatively slow decay kinetics. Hence, NMDA‐Rs are critical for maintaining action potential generation at high firing rates. These results demonstrate a novel role for NMDA‐Rs enabling a high probability of release synapse to maintain the fidelity of synaptic transmission during high frequency firing when glutamate release and AMPA‐R responses are reduced. They also suggest why NMDA‐Rs are critical for responses that may depend on high rates of afferent discharge.